Measuring the Impact of Loan-to-Deposit Ratio (LDR) on Banks’ Liquidity in Nepal - Rana, Ishwari; Paudel, Garima; Chauhan, Jyoti; Panta, Jyoti (Nepalese Journal of Finance, 2025)
This study examines the effect of loan to deposit ratio on the liquidity of Nepalese commercial banks. Liquid deposit to total deposit and cash reserve ratio are selected as the dependent variables. The selected independent variables are loan to deposit ratio, capital adequacy ratio, return on assets, non-performing loans, firm size and interest rate. The study is based on secondary data of 10 Nepalese commercial banks with 100 observations for the period from 2014/15 to 2023/24. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of loan to deposit ratio and other bank specific factors on the liquidity in Nepalese commercial banks. The study showed that return on assets has a positive impact on liquid deposit to total deposit and cash reserve ratio. It indicates that increase in return on assets lead to increase in liquid deposit to total deposit liquid deposit to total deposit and cash reserve ratio. However, interest rate has a negative impact on liquid deposit to total deposit liquid deposit to total deposit and cash reserve ratio. It indicates that increase in interest rate leads to decrease in liquid deposit to total deposit liquid deposit to total deposit and cash reserve ratio. In contrast, capital adequacy ratio has a positive impact on liquid deposit to total deposit liquid deposit to total deposit and cash reserve ratio. It indicates that increase in capital adequacy ratio leads to increase in liquid deposit to total deposit liquid deposit to total deposit and cash reserve ratio. However, loan-to-deposit ratio has a negative impact on liquid deposit to total deposit liquid deposit to total deposit and cash reserve ratio. It indicates that increase in loan-to-deposit ratio leads to decrease in liquid deposit to total deposit liquid deposit to total deposit and cash reserve ratio. In contrast, firm size has a positive impact on liquid deposit to total deposit liquid deposit to total deposit and cash reserve ratio. It indicates that higher the firm size, higher would be the liquid deposit to total deposit liquid deposit to total deposit and cash reserve ratio. However, non-performing loan has a negative impact on liquid deposit to total deposit liquid deposit to total deposit and cash reserve ratio. It indicates that increase in non-performing loan leads to decrease in liquid deposit to total deposit liquid deposit to total deposit and cash reserve ratio.